Mechanical Properties Of Chemically Modified Portuguese Pinewood - B.Lopes, Duarte; Mai, Carsten; Militz, Holger (Maderas. Ciencia y Tecnología, 2015)
To turn wood into a construction material with enhanced properties, many methods of chemical modification have been developed in the last few decades. In this work, mechanical properties of pine wood were chemically modified, compared and evaluated. Maritime pine wood (Pinus pinaster) was modified with four chemical processes: 1,3-dimethylol-4,5-dihydroxyethyleneurea, N-methylol melamine formaldehyde, tetra-alkoxysilane and wax. The following mechanical properties were assessed experimentally: Modulus of elasticity measured statically, stiffness stabilization efficiency in different climates (30 and 87% of relative humidity), modulus of rupture, work maximum load, impact bending strength, compression, tensile and shear strength at indoor conditions (65% of relative humidity). In both types of active principle of modification, cell wall or lumen fill, no significant changes on the bending stiffness (modulus of elasticity) were found. In the remaining properties analysed significant changes in the modified wood-material took place compared to unmodified wood control: - Cell wall modification was the most effective method to achieve high stiffness stabilization efficiency (up to 60%) and also increased compression strength (up to 230%). However, modulus of rupture, tensile, shear and the impact bending strength were reduced by both resins, but in a varying extent, where the N-methylol melamine formaldehyde endured less reduction than 1,3-dimethylol-4,5-dihydroxyethyleneurea resin. In the latter, reduction up to 60% can take place. - In the lumen fill modification: tetra-alkoxysilane has no effect in the mechanical properties. Although, a slight increase in shear strength parallel to the grain was found. Wax specimens have shown a slight increase in bending strength, compression, tensile and shear strength as well as in the absorption energy capacity.